Effect of Dopant Concentrations on Magnetic States of Ti, Mn, And Ni Doped Iii-V Zincblende Compounds - Shahjahan, M; Khan, T; Rahman, MM (Journal of Bangladesh Academy of Sciences, 2018)
The effect of Ti, Mn, and Ni dopants concentration on various magnetic states of III-V zincblende compounds (Al1-xTx)M is presented by calculation of multiple scattering theory based on Korringa–Kohn–Rostoker coherent potential approximation (KKR-CPA), where T denotes Ti, Mn, and Ni atoms and M represents As and P atoms. The calculations reveal the phase changes in various magnetic states, which are solely controlled by dopant concentrations. The turning points of these behaviors are reported, which are responsible for the change of stable ferromagnetic (FM) state to unstable disordered local moment (DLM) state. The Curie temperature, magnetic moments, and density of states at different concentrations of the dopants are calculated and explain the concurrency with magnetic phase stability. Journal of Bangladesh Academy of Sciences, Vol. 42, No. 2, 177-182, 2018